(3Gdeage deG CTcd ef cJGH eSde (B( (3GdUMjM(B)s - (3CMeO Hf YeQ Hf EHQGgje GdbQWHis; (3GdQGYj , eMeO Hf eMeO Hf eMeO Hf ESeGYjd GdCfOdSj GdZQfGWj, TeS GdOjf CHh YHO Gddg,J (B853 (3g` s ((3eMeO Zfje s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje cJGH GdMOhO hgj LejY MO hCUd GdMO GdefY MjK hbY hEf GNJdaJ CHfjI hUjZI hSejJ GdYbhHGJ s
(3BNQgG (B:s
(3jfJgi HPcQ aVGFd SYO Hf CHj hbGU Hbhdg (B: (3hjMUd ef ahGFO GdBjI hGdMOjK Gdfgi Yfg Cf jYXe CMO dLGgg hCKhGHg Je GdLRA GdQGHY s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B47 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B271s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs